Potential modulation of cancer progression by oxysterols. (June 2016) - Poli, Giuseppe; Biasi, Fiorella
Abstract: At least with regard to promotion and progression of cancer, oxysterols actually appear as typical Janus molecules, by inducing early inflammatory reaction against cancer expansion and apoptotic death of cancer cells, but on the other hand sustaining a complex survival signaling pathway that eventually turns in favor of the neoplastic process itself. The pro-tumoral and anti-tumoral properties of this class of compounds is mediated by both LXR-dependent and independent mechanisms. The extent of oxidative redox imbalance, moderate or extensive, likely plays a key role in determining the actual effects operated by oxysterols along the various steps of carcinogenesis.